2021
DOI: 10.1111/jvim.16321
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of cystoscopic‐guided laser ablation of intramural ectopic ureters in female dogs

Abstract: Background Cytoscopic‐guided laser ablation (CLA) is a technique that can be used to correct intramural ectopic ureters (EUs) in dogs. Hypothesis/Objectives To describe clinicopathologic, imaging, and cystoscopic findings in dogs undergoing CLA for intramural EU correction, and whether any of these findings are associated with continence outcomes. Animals Thirty‐one client‐owned dogs undergoing CLA between 2009 and 2019. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…These findings prompt us to recommend CLA to treat iEU in female dogs. In contrast to previous studies, fluoroscopy was not used in the present study 10,11,14,19 . This imaging modality may be used to confirm the anatomical position of the ureter and confirm the correct position of the newly formed ureterovesical junction within the bladder, potentially reducing the risk of urethral tear during CLA 20 …”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…These findings prompt us to recommend CLA to treat iEU in female dogs. In contrast to previous studies, fluoroscopy was not used in the present study 10,11,14,19 . This imaging modality may be used to confirm the anatomical position of the ureter and confirm the correct position of the newly formed ureterovesical junction within the bladder, potentially reducing the risk of urethral tear during CLA 20 …”
Section: Discussionmentioning
confidence: 96%
“…Several studies have previously reported the use of CLA for iEU correction in both female and male dogs. 10,11,14,19,20 Proposed advantages of CLA include its minimally invasive nature, the ability to diagnose and treat the EU simultaneously and resect the entire length of some distally opening iEU. Nearly 90% (8/9) of dogs treated by CLA were continent at short-term evaluation in our study although no difference in incontinence persistence after iEU correction was detected when compared to dogs treated with neoureterostomy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations